FACTORS DETERMINING THE DECISIONS FOR PROVIDING PEOPLE'S BUSINESS CREDIT (KUR) FISHERMAN HOUSEHOLDS IN BENGKULU PROVINCE - Pratama, Edo Putra; Reswita, Reswita; Khairani, Lathifah; Istriningsih, Istriningsih (Jurnal Perikanan Unram, 2025)
Credit involves a component of trust that an organization or bank places in its customers. One form of credit provision for the public is the People’s Business Credit (KUR). This study focuses on the decision-making process for granting KUR to fishing households in Bengkulu Province. The objective of this research is to provide a descriptive analysis of KUR distribution to fishing households and to identify the factors influencing credit approval decisions. This study was conducted in Bengkulu Province, which was purposively selected due to the broader availability of KUR capital. The research utilizes secondary data, with analytical methods including descriptive statistics and binary logistic regression. The findings indicate that 42 fishermen (21%) received KUR, while 158 fishermen (79%) did not. The factors that significantly influence the probability of receiving KUR are age and bank account ownership. Banks should implement policies that allow alternative requirements to replace collateral, ensuring that fishermen in Bengkulu Province can meet the necessary conditions. This study can serve as a reference for future research, which can be further explored using primary data.